Dispersals of the Siberian Y-chromosome haplogroup Q in Eurasia - Huang, Yun-Zhi; Pamjav, Horolma; Flegontov, Pavel; Stenzl, Vlastimil; Wen, Shao-Qing; Tong, Xin-Zhu; Wang, Chuan-Chao; Wang, Ling-Xiang; Wei, Lan-Hai; Gao, Jing-Yi; Jin, Li; Li, Hui (Molecular genetics and genomics, 2018)
The human Y-chromosome has proven to be a powerful tool for tracing the paternal history of human populations and genealogical ancestors. The human Y-chromosome haplogroup Q is the most frequent haplogroup in the Americas. Previous studies have traced the origin of haplogroup Q to the region around Central Asia and Southern Siberia. Although the diversity of haplogroup Q in the Americas has been studied in detail, investigations on the diffusion of haplogroup Q in Eurasia and Africa are still limited. In this study, we collected 39 samples from China and Russia, investigated 432 samples from previous studies of haplogroup Q, and analyzed the single nucleotide polymorphism (SNP) subclades Q1a1a1-M120, Q1a2a1-L54, Q1a1b-M25, Q1a2-M346, Q1a2a1a2-L804, Q1a2b2-F1161, Q1b1a-M378, and Q1b1a1-L245. Through NETWORK and BATWING analyses, we found that the subclades of haplogroup Q continued to disperse from Central Asia and Southern Siberia during the past 10,000 years. Apart from its migration through the Beringia to the Americas, haplogroup Q also moved from Asia to the south and to the west during the Neolithic period, and subsequently to the whole of Eurasia and part of Africa.
Keywords: Asia; Chromosomes, Human, Y; lidský chromozom Y; Eurasia; China; jednonukleotidový polymorfismus; Sibiř; Human Migration; Multidirectional migrations; lidé; Polymorphism, Single Nucleotide; Han Chinese; Haplogroup Q; Siberia; Phylogeny; Genetics, Population; Haplotypes; Microsatellite Repeats; Čína; Y-chromosome; Asie; haplotypy; migrace lidstva; fylogeneze; mikrosatelitní repetice; populační genetika; Humans